Can Lawlike Rules Emerge without the Intervention of Legislators? - Troitzsch, Klaus G. (Frontiers in Sociology, 2018)
The paper shows that in an artiﬁcial society lawlike rules emerge “as a result of individual action but without being designed by any individual” agents [Hay44, p. 288] and discusses earlier literature on the topic. The ﬁrst example which this paper uses is an artiﬁcial society of car drivers moving between their homes and their working places on streets with two lanes crossing each other at right angles. Car drivers start using the left or right lane of the street at random and continue to use the same side of the street until they are stopped by an oncoming car. In this occasion one them decides to change to the other side of the street, taking into account which side of the street is used by the locally visible majority. This very simple behaviour usually results in a society- wide applied rule: always using the same side of the street. How long it takes for all car drivers to abide by the emerged rule (and how many, if not all, apply the rule) depends on the density of trafﬁc and the range of vision of the car drivers as well as on the distance the cars went. A second example of emerging rule-consistent behaviour discussed in the pa- per and analysed with different mathematical and computational methods is de- rived from a model of the the emergence of aggression aversion extended to a model of the emergence of a rule against theft and of a rule in favour of almsgiv- ing. In this model agents receive comments on their theft and alms related actions and form a normative board which controls their propensity to act with respect to theft, prosecuting and punishing theft, asking for and granting alms. This model shows an emerging ant-theft norm whose salience among the agents increases in a rapid transition after a fairly long initial phase during which theft is more or less tolerated.